2018
DOI: 10.1177/0260106018815392
|View full text |Cite
|
Sign up to set email alerts
|

Folate and vitamin B12 status and their relation to hematological indices in healthy adults of Iranians: Azar cohort study

Abstract: Background: Folate and vitamin B 12 are essential micronutrients, the deficiency of which can be associated with public health problems worldwide. Aim: The aims of this study were to assess the folate and vitamin B 12 status of healthy adults and the effect of gender differences on their deficiency using serum folate, vitamin B 12 and red blood cell (RBC) folate as biomarkers and their relation to hematological indices. Methods: This study was a part of the Azar cohort study, which is designed as a noncommunic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
13
1
1
Order By: Relevance
“…We observed that only 2.8% of the tested patients revealed low folate serum levels. Azimi et al (2019) reported a higher prevalence of folate and vitamin B12 deficiency in healthy adults (sample of 95 healthy adults) from Iran reporting low serum concentrations of folate and vitamin B12 in 16.8% and 6.1% of the patients, respectively. The authors reported that hemoglobin concentration, but not MCV, correlated with folate and vitamin B12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that only 2.8% of the tested patients revealed low folate serum levels. Azimi et al (2019) reported a higher prevalence of folate and vitamin B12 deficiency in healthy adults (sample of 95 healthy adults) from Iran reporting low serum concentrations of folate and vitamin B12 in 16.8% and 6.1% of the patients, respectively. The authors reported that hemoglobin concentration, but not MCV, correlated with folate and vitamin B12.…”
Section: Discussionmentioning
confidence: 99%
“…Some research studies performed in countries of the middle east showed that the prevalence of folate deficiency has been found to be on higher side ( Azimi et al, 2019 ). It has been suggested that Saudi Arabia shows high prevalence of folate deficiency, however no epidemiological studies have been performed to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In general, malnutrition is implicated in the disease progression and is associated with poor outcome. 19 16,20 There is limited data regarding vitamin B12 efficacy in COVID-19 treatment, and its therapeutic role in this disease is a matter of debate. 21 Due to this controversy, and for the development of new treatment protocols for COVID-19 treatment, the present study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Lower hemoglobin levels that is not accompanied by a decrease in serum ferritin indicates the occurrence of non-iron deficiency anemia. The decrease in hemoglobin may be due to deficiencies of other nutrients besides iron, such as lack of intake of protein which is also a component of iron, deficiency of B12, or folic acid, or there is an inflammatory reaction due to certain infections [12], [13], [14].…”
Section: Discussionmentioning
confidence: 99%